Mediating role of formalization of RM methods among the perceived business risk and organization performance - Akmal Shahzad; Bushra Zulfiqar; Mumtaz Ali; Ayaz ul Haq; Maryam Sajjad; Ahmad Raza (Cogent Business & Management, 2022)
The rapid changes in technology and globalization lead to mediating role in formalization of RM methods among perceived business risk and organization performance. Questionnaire distributed among 301 financial professionals of selected industries and duly filled questionnaires received back 204. Pilot study was conducted at 96 responses to check the validity and reliability of instrument. Questionnaire distributed among CFOs/Finance managers/Risk Managers of selected industries. The study results imply that the performance of the organization has a significant positive relationship with all components of perceived Business risk (PBR) such as economic factors, financial indicators, technological change, political uncertainty, and market competition. It is also found that the Formalization of RM Methods mediates among the component of PBR and organization performance. The results provide meaningful insights for managers, which are used generally by any organization as a guideline to improve the organization's performance.
Keywords: 650; formalization of RM methods; organization performance; Perceived business risk; risk management